FACTORS ASSOCIATED WITH SEVERE ACUTE MALNUTRITION AMONG CHILDREN AGED 6 MONTHS TO 59 MONTHS ATTENDING MOROTO REGIONAL REFERRAL HOSPITAL MOROTO MUNICIPALITY. A CROSS-SECTIONAL STUDY. - Laalany , Daniel (Student’s Journal of Health Research Africa, 2023)
Background: Objectives: Study established factors associated with SAM among children aged 6 months to 59 months attending Moroto Regional Referral Hospital. The specific objectives of the study were to assess demographic, socioeconomic, and clinical factors associated with SAM among children aged 6-59 months attending MRRH, Moroto municipality in the Karamoja sub-region. Methodology: The study used a descriptive cross-sectional design. A convenience sampling technique was used. A target population of 152 respondents was included in the study. Research-based questionnaires were used to collect data from the respondents. Data were analyzed using SPSS software. Results: The prevalence of SAM in children aged 6-59 months attending MRRH is 34.2%. The following factors were significantly associated with SAM: birth order 1-3rd 61.5%, birth interval <2 years 48.1%, rural setting 84.6%, no education background 92.3%, no occupation 82.7%, no stable family income 92.3%, family members >5 71.2%, unsafe source of water 76.9%, breastfeeding < 8 times 69.2%, early or delayed weaning 78.8%, previous infection 67.3%, diarrhea for >1 week 46.3%. Conclusions: The findings of this study indicated that birth order, birth interval residence, education level, oc- cupation, family size, source of water, age of weaning, frequency of breastfeeding, previous infections, and diarrhea were major factors associated with SAM among children aged 6-59 months. Recommendations: Government through the Ministry of Health should resort to mass screening of children in the Karamoja region to combat the increasing prevalence of SAM in Karamoja. Health education on the importance of family planning should be passed on to them to correctly plan for good birth intervals and manageable family sizes. Emphasis on education for all should be put in place. Management of the underlying conditions, and health education on the importance of breastfeeding should be put in place to fight this epidemic.